2019
DOI: 10.22146/majkedgiind.37414
|View full text |Cite
|
Sign up to set email alerts
|

Effect of advanced platelet-rich fibrin applications on periodontal regeneration in infrabony pocket treatment

Abstract: One of the regenerative periodontal treatments for infrabony pocket is open flap debridement (OFD) with the addition of growth factor derived from platelet concentrate. Advanced platelet-rich fibrin (A-PRF) is a further development of plateletrich fibrin (PRF) with a lower centrifugation speed (1,500 rpm, 14 minutes). The purpose of this study was to examine the differences in periodontal tissue regeneration after the application of A-PRF and PRF in the treatment of infrabony pockets evaluated from probing dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…When compared to PRF, A-PRF improves periodontal weakened sites by regenerating tissues by increasing parameters like probing depth, lowering relative attachment loss, and increasing bone height, which is similar to infrabony pocket treatment [8]. A-PRF improves soft tissue recovery at extraction sites and reduces postoperative discomfort and the requirement for analgesics [7].…”
Section: Clinical Applicationsmentioning
confidence: 97%
“…When compared to PRF, A-PRF improves periodontal weakened sites by regenerating tissues by increasing parameters like probing depth, lowering relative attachment loss, and increasing bone height, which is similar to infrabony pocket treatment [8]. A-PRF improves soft tissue recovery at extraction sites and reduces postoperative discomfort and the requirement for analgesics [7].…”
Section: Clinical Applicationsmentioning
confidence: 97%
“…A-PRF was found to contain increased levels of VEGF, responsible for angiogenesis, monocytes as a source for bone morphogenetic proteins (BMPs), and fibronectin for extracellular matrix formation [ 9 , 10 , 11 ]. Various in vitro and in vivo studies have shown the positive outcomes with A-PRF in hard and soft tissue regeneration [ 12 , 13 , 14 , 15 , 16 ]. However, the potential benefit of A-PRF in management of gingival recession has not yet been established.…”
Section: Introductionmentioning
confidence: 99%
“…18 The different number of growth factors between A-PRF and PRF is enough to make significant differences in the value of PD and RAL according to Suwondo et al (2018) who compared OFD + PRF and OFD + A-PRF. 10 1.2% rosuvastatin gel was added in both groups in this study to maximize healing process and regeneration of soft and hard periodontal tissues. The pleiotropic effects of 1.2% rosuvastatin gel, such as antioxidants, anti-inflammation, osseo-modulation, and immunomodulation play role in the healing process of periodontal tissues by modifying host regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no difference in the increase in alveolar bone height because PRF only had an effect on the first initial stage, i.e., osteogenesis phase by optimizing osteoblast diffierentiation. 10 Pradeep et al (2016) showed that OFD + PRF + 1.2% rosuvastatin (RSV) gel was able to decrease the value of clinical attachment level (CAL) and PD and significantly repair the infrabony defect better than OFD + PRF and OFD treatment. 4 The 1.2% RSV gel acts as host modulation therapy which aims to reduce tissue damage and regenerate the inflamed tissue by modifying the response of host factors.…”
Section: Introductionmentioning
confidence: 99%